The Cult of the Supreme Being as a Unification of Secular Philosophy and Religious Worldview: Civil Religion as a Justification of the Reign of Terror - Anna Kurilenko (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия, 2025)
This article outlines the possibility of describing the cult of the Supreme Being as a derivative of religious and enlightenment worldviews. The cult of the Supreme Being, which emerged in the context of the policy of revolutionary dechristianization and, more broadly, in the process of secularizing socio-political life, was supposed to provide some new justification for suffering, which is an integral part of the human experience. The idea of a civil religion proposed to the Convention served as a means of overcoming the spiritual schism of French society, supporting civic virtues during the war, and as an unofficial religious justification for the political campaign of the Jacobins that had begun, the Terror. The speeches of Robespierre, the author of the cult of the Supreme Being, as well as the documents describing the celebration of the new deity, can be seen as having a strong influence of Rousseau's ideas on the philosophical thought of the French revolutionary. Robespierre follows him in his attempts to “purify” or de-dogmatize Christianity, returning it to the state of “natural religion”. Yet, his project can still be called original. By adapting the cult to the needs of the state, he insists on its strict centralization and building a hierarchy for political purposes. The cult of the Supreme Being as a "natural religion", more of a philosophical than a religious idea, inherits both the Protestant aspirations of Rousseau and the Catholic experiences of Robespierre himself. This complex heritage can explain its ideological inconsistency; on the one hand, it is based on the secular idea of undamaged human nature, on the other hand, it maintains a pessimistic outlook on the ability of an individual to perform moral acts. Reason, which was considered the basis of ethical behavior in the Age of Enlightenment, is rejected by Robespierre, who postulates that morality must rely on a deeply rooted moral feeling. Force, external to the individual, is needed to ensure happiness and maintain virtue. The state, not the church, guarantees order and justice. The Supreme Being acts as the highest official in this project, as a posthumous judge, preserving the highest justice in the Reign of Terror. Thus, Robespierre's civil religion truly unites the Enlightenment attitude to life and remains of the Christian view of man.